Colorado pet owners' perceptions of and attitudes towards antimicrobial drug use and resistance. (24th January 2023) - Taylor, Daniel D.; Scallan Walter, Elaine J.
Abstract: Background: Antimicrobial drug (AMD) use in companion animal medicine may contribute to antimicrobial resistance (AMR) in both pets and humans. However, pet owners' attitudes and perceptions regarding AMD use and AMR have not been extensively studied in the United States. Methods: A cross‐sectional survey at five Colorado veterinary hospitals collected information about pet owners' knowledge and perceptions of AMD use and AMR, adherence with AMD treatment instructions and the role of the veterinarian in the AMD prescribing process. Results: The pet owners surveyed did not have an adequate understanding of AMR and were unaware of the potential human health impact of AMD use in pets. However, most pet owners reported adherence with veterinary prescription instructions and indicated that they trusted their veterinarian to make appropriate decisions for their pets. Limitations: The cross‐sectional design focusing on Colorado pet owners limits the generalisability of the results. Selection and social desirability biases may have occurred, which could have affected who participated and how participants responded to statements. Conclusions: Pet owners play an important role in the AMD prescription process, and their lack of AMR understanding should be addressed in antimicrobial stewardship plans. Further research on how to effectively incorporate pet owners into stewardship interventions is needed.